Process and personality : actualization of the personal world with process-oriented methods - Smith, Gudmund J. W.; Carlsson, Ingegerd M. (Process thought, 2008)
This book is a joint effort of like-minded researchers to define the concept of process within a psychological setting. Although minor differences exist as regards choice of background theory, their common focus is on personality in a broad psychodynamic context. Their definition of personality rests on a series of test instruments that have been validated during decades of thorough and vigorous empirical work. These were originally designed to open up micro-processes underlying the adaptation to or construction of reality, and have subsequently proven diagnostically efficient. Coming from bot.